Forage Production and Nutrient Composition of Different Sorghum Varieties Cultivated with Indigofera in Intercropping System - M. Telleng; K. G. Wiryawan; P. D. M. H. Karti; I. G. Permana; L. Abdullah (Faculty of Animal Science, Bogor Agricultural University, 2016)
The experiment aimed to evaluate the production of nutrients by different varieties of sorghum grown with high valuable indigofera legume in intercropping system and to determine the suitable variety of sorghum that produced the highest nutrient in the system. The experiment was done at Jonggol Animal Science Teaching and Research Unit (UP3J) Jonggol, from November 2014 to March 2015. This experiment was conducted using completely randomized design with 2 factors (3 x 4) and 4 replications. The first factor was sorghum varieties (PATIR 3.2 (S1), PATIR 3.7 (S2), and CTY-33 (S3)). The second factor was indigofera composition (0% indigofera (I0), 30% indigofera (I1), 40% indigofera (I2), and 50% indigofera (I3)). Data were analyzed using analysis of variance and HSD test. There was no interaction among varieties of sorghum and indigofera composition. Indigofera population of up to 50% in multiple cropping system had the highest (P<0.01) dry matter content, crude protein content, ash content, total fresh weight production, total dry weight production, total crude protein production, total ash production, and carrying capacity. Sorghum variety CTY-33 planted in multiple cropping system had the highest (P<0.01) dry matter content, total dry weight production, and (P<0.05) total crude protein production. PATIR 37 sorghum variety planted in multiple cropping system had the highest (P<0.05) ash content and (P<0.01) total ash production. It is concluded that Indigofera population of up to 50% planted with different varieties of sorghum in multiple cropping system had the highest nutrient production.